Plasma-functionalized exfoliated multilayered graphene as cement reinforcement. (1st March 2019) - Dela Vega, Ma. Shanlene D.C.; Vasquez, Magdaleno R.
Abstract: A fast, facile, nonhazardous, environment-friendly, and high yield process was developed for the plasma treatment of graphite particles and the production of plasma-functionalized multilayered graphene (pf-MLG). Graphite particles (< 20 μ m) were functionalized using a subatmospheric 13.56 MHz radio frequency-excited oxygen plasma followed by liquid-phase exfoliation to produce pf-MLG with a high aspect ratio (> 2585) with< 20 graphene layers. The exfoliated graphene also exhibited high dispersibility in water after plasma functionalization without the use of surfactants. The pf-MLG nanoflakes were incorporated into a cement mixture with 0.1 and 0.5 wt% pf-MLG loading. A 56% increase in compressive strength of cement mortars was achieved for the 0.5 wt% pf-MLG after 28 days curing. This is attributed to the strong interfacial interaction between graphene and the cement matrix and the promotion of hydration. The highly scalable process of pf-MLG-reinforced cement will make a positive impact on the environment, especially in the construction industry.